Innovative approaches to service integration addressing the unmet needs of irritable bowel syndrome patients and new approaches for the needs of IBS patients - Gentile, Maurizio; De Luca, Vincenzo; Patalano, Roberta; Laudisio, Daniela; Tramontano, Giovanni; Lindner-Rabl, Sonja; Mercurio, Lorenzo; Salvatore, Elena; Farrell, John; Roller-Wirnsberger, Regina; Kubitschke, Lutz; Triassi, Maria; et al. (Frontiers in Medicine, 2022)
Abstract: Background : Irritable bowel syndrome (IBS) is a common multifactorial condition that affects the large intestine and is characterized by chronic and relapsing abdominal pain and altered bowel habit. IBS is due to a combination of genetic, environmental and dietary factors. It's usually a lifelong problem very frustrating to live with and can have a big impact on quality of life, as single-agent therapy ra: Objective to analyze the approaches and solutions that address the social and health unmet needs of patients with IBS. Design: A quantitative-qualitative approach was adopted in the current study to identify and specify key digital solution and high impact user scenarios applied to IBS patients, through an adaptation of the “Blueprint on Digital Transformation in Health and Care in an Ageing Society” persona methodology. Settings: Digital health solutions bring the potential of supporting health interventions through mobile apps, wearable devices, telemedicine. Patients: A Survey was administered to a group of patients in an anonymous form, and no need for Medical Ethical Committee approval was identified. Interventions. The theoretical elaboration IBS personas was developed through an interdisciplinary Focus Group, which also mapped the pathway for the patient's management. Main Outcome : Three main needs were identified to be met to improve IBS patient’s lifestyle: access to psychological support, mHealth solutions supporting diet and adapted physical activity, and home-based digital health support. mHealth intervention has been identified for diet adherence, physical exercise and psychological well-being. The process has been mapped and adapted to integrate the new solutions into the care pathway. Limitation: Further research is needed to evaluate how mHealth services enable IBS patients to manage their conditions and improve their quality of life. Conclusion The person-centered approach was implemented through a multidisciplinary Focus group that enabled the identification of the need for a mHealth intervention